2009
DOI: 10.1088/0957-4484/21/3/035707
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport through single-wall carbon nanotube–anodic aluminum oxide–aluminum heterostructures

Abstract: Aluminum foils were anodized in sulfuric acid solution to form thick porous anodic aluminum oxide (AAO) films of thickness approximately 6 microm. Electrodes of carboxyl-functionalized single-wall carbon nanotube (SWCNT) thin films were inkjet printed on the anodic oxide layer and the electrical characteristics of the as-obtained SWCNT-AAO-Al structures were studied. Nonlinear current-voltage transport and strong temperature dependence of conduction through the structure was measured. The microstructure and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, exploiting the unique properties of CNTs (electrical conductivity, porous structure, flexibility, etc.) requires their immobilization on various substrates in a controlled manner either by deposition [13][14][15], transfer [16][17][18][19][20][21] or by direct synthesis [22][23][24] with well-defined structure and geometry. In electrical applications, the contact resistance at the substrate-CNT interface [2,17,25], mechanical robustness and integrity [17,26] as well as charging/discharging behavior of the devices [9][10][11][12] are among the most important parameters to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…However, exploiting the unique properties of CNTs (electrical conductivity, porous structure, flexibility, etc.) requires their immobilization on various substrates in a controlled manner either by deposition [13][14][15], transfer [16][17][18][19][20][21] or by direct synthesis [22][23][24] with well-defined structure and geometry. In electrical applications, the contact resistance at the substrate-CNT interface [2,17,25], mechanical robustness and integrity [17,26] as well as charging/discharging behavior of the devices [9][10][11][12] are among the most important parameters to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Since carbon nanotubes were first discovered, 1 there has been much work on the behavior of nanotubes. [2][3][4][5] It has been found that nanotubes not only have many properties in common with a wide range of nanomaterials, such as quantum size effects, surface effects and macroscopic quantum tunneling, but also display potentially useful properties, for instance, direct electronic transmission and biological compatibility. 6 The special tubular structure is also of great interest.…”
mentioning
confidence: 99%
“…Most importantly, the peaks observed on high resolution O 1 s spectra were attributed to AAO moieties and organic oxygen moieties were not detected (Supplementary Fig. 3c ) 42 . We also measured the ultraviolet-visible (UV-Vis) spectra of AAOCN and blank AAO membranes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%